(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Purpose: The aim of present work was to investigate the in vitro release profile of diclofenac sodium from matrix tablets,which were prepared using guar gum with and without probiotics. Methods: Six matrix tablets formulations (F1-F6) of diclofenac sodium containing varying proportions of guar gum, 10-60% of tablet weight were prepared by wet granulation method and evaluated in vitro for their release profile. Four matrix tablets formulations (F7-F10) of diclofenac with guar gum (40%) were prepared incorporating varying concentration of commercial spores of lactobacillus and bifidobacterium species that are commonly found in colon microflora. Results: The tablets having same concentration of guar gum without probiotics (F4) showed a 54.47% cumulative release of diclofenac after 24 hr while that in presence of probiotics (F9) was 73.01%. These drug release studies were conducted without rat caecal content. In another set of experiments, the drug release studies were carried out in presence of rat caecal content. In such experiments, more than 95% drug was released from F4 and F9 formulations after 24 hr. Conclusion:The results showed that commercial probiotics are capable in digesting guar gum. These probiotics may be used to assist in colon delivery of drugs from formulations prepared with guar gum.